Analysis of the Clinical Efficacy of Interlock Detachable Coil Interventional Embolization on Pelvic Congestion Syndrome and Ovarian Reserve Function: A Retrospective Study - Wang P; Zheng XL; Wang YH; Tao Y; Wang WC (International Journal of General Medicine)
Peng Wang,1,2 Xiang-Long Zheng,1 Yu-Huan Wang,1 Yun Tao,2 Wan-Chun Wang3 1Clinical Medical College, Jiangxi University of Chinese Medicine, Nanchang, People’s Republic of China; 2Department of Interventional and Vascular Surgery, Affiliated Hospital of Jiangnan University, Wuxi, People’s Republic of China; 3Department of Traditional Chinese Medicine Surgery, Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang, People’s Republic of ChinaCorrespondence: Wan-Chun Wang, Department of Traditional Chinese Medicine Surgery, Affiliated Hospital of Jiangxi University of Chinese Medicine, 445 Bayi Avenue, Nanchang City, Jiangxi, 330006, People’s Republic of China, Email wwjx7469108@163.comObjective: This study aimed to examine the effects and the efficacy of a combination of interventional embolization and endocrine hormone therapy for Pelvic congestion syndrome (PCS).Methods: We retrospectively analyzed 132 patients diagnosed with PCS, and divided them into three groups based on their therapeutic schedule. The visual analog scale (VAS), pelvic venous blood flow parameters, and serum hormone levels of the three groups were compared before and after treatment. Moreover, the clinical efficacy and long-term changes in ovarian reserve functions were analyzed. For the comparison of measurement data before and after treatment within the group, paired - sample t - test was used for analysis. For the comparison between groups, one - way analysis of variance was applied. A P - value less than 0.05 indicated a statistically significant difference.Results: Patients in the study group had significantly lower pain degrees than in the control group I and the control group II at 24 h and the first month after the operation (p < 0.05). The degree of pain in patients in the study group was significantly lower than that in the control group I at the third and 6 months following the treatment (p < 0.05). The parameters of venous blood flow and ovarian reserve in patients treated with the combined endocrine hormone therapy were significantly better than those in patients not treated with endocrine hormone therapy (p < 0.05). The total effective rate of the study group was significantly higher than that of the control groups (p < 0.05).Conclusion: A combination of precise interventional embolization and endocrine hormone therapy can rapidly and effectively relieve pain in patients with PCS. Compared with free coil embolization, this combination can effectively increase vascular tension, reduce congestion, inhibit ovarian function, reduce pelvic congestion, and relieve symptoms.Keywords: endocrine hormone therapy, interventional embolization, interlock detachable coil, ovarian reserve function, pelvic congestion syndrome